Implementasi Kurikulum Merdeka Belajar Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa SMA Melalui Pembelajaran Project Based Learning - Galuh Prabowo; Muh. Imam Khaudli (Jurnal Pendidikan Indonesia (JOUPI), 2024)
The Independent Learning Curriculum is a new idea in Indonesian education that is very welcome. This curriculum offers more student-centered and meaningful learning because it was made with flexibility and relevance in mind. Turning the back of your hand is not an easy way to use it, though. A method of learning that fits with the Independent Learning Curriculum is project-based learning. Students are at the heart of project-based learning, which puts them in charge of their own learning and lets them learn through real-life projects. Teachers play a big part in helping their students learn how to think critically. This kind of study is called qualitative research. If you want to do descriptive research, you can get written or spoken words from people and facts from their actions that you can see. This is what qualitative research means. Project-based learning is a new and interesting way to learn, according to the results of this study. Students are more likely to learn when they are working on projects that involve fixing problems from real life. Project-based learning tries to use the real world as a teaching tool. No longer do students learn vague ideas that have nothing to do with their everyday lives. Students work in groups to finish real projects in project-based learning. This process teaches them to accept each other's opinions, talk to each other clearly, and come to an agreement.